Ethical Review of Telemedicine Practices in Healthcare Services in Indonesia Using the Natural Law Theory Approach - Agus Santoso, Aris Prio; Sukendar, Sukendar (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
The lack of comprehensive integration between ethical and legal dimensions in the regulation and practice of telemedicine in Indonesia highlights the need for in-depth analysis based on the principles of Natural Law to ensure justice, patient rights protection, and medical accountability. This study employs a descriptive qualitative method with a conceptual approach grounded in Natural Law Theory to assess the extent to which telemedicine regulations reflect universal moral values. The findings indicate that telemedicine development must be rooted in core medical ethics principles such as justice, beneficence, non-maleficence, autonomy, and patient privacy, principles that represent expressions of natural moral law. According to Thomas Aquinas, health policies that deviate from these moral principles lose their legitimacy as they contradict reason and the common good. Therefore, telemedicine policy must not only focus on technical aspects and efficiency but also uphold human dignity and justice. This Natural Law approach enables Indonesia to build a technology-based healthcare system that is not only legally valid but also fundamentally moral and just.